ASEAN’S HUMAN RIGHTS BODY: NEW BREAKTHROUGH FOR HUMAN RIGHTS PROTECTION IN SOUTH EAST ASIAN REGION SOME PRELIMINARY NOTES FROM INDONESIA’S PERSPECTIVE - Afriansyah, Arie (UI Scholars Hub, 2011)
On 21 November 2007, leaders of the Association of South East Asian Nations (ASEAN) promulgated the ASEAN Charter (the Charter). Not only does it provide legal basis for ASEAN’s legal personality; it also provides new legal norms for its member states. One of those that need to be discussed is the establishment of ASEAN’s Human Rights Body (the Body). This obligation is stipulated in Article 14 of the Charter, which stresses the commitment of member nations to protect human rights. However, the establishment of the Body has faced numerous pessimistic opinions regarding the organisation’s capability to protect human rights considering its notorious reputation over this matter. The article is fosucing on some areas of concerns that need to be looked at to put the Body into operation. Some important lessons from the European Human Rights Body is examined as comparison.